Building on Early Gains in Afghanistan's Health, Nutrition, and Population Sector : Challenges and Options - Belay, Tekabe A. (World Bank, 2012)
A number of development partners, including the World Bank, have been actively supporting the health sector in Afghanistan since 2003-04 (1382 AC). Collectively, they invested more than $820 million between 2003 (1382 AC) and 2008-09 (1387 AC) and played key roles in supporting the government in reshaping the country's health sector. This support continues, with all partners starting new projects aimed at further strengthening the sector and building on the successes that have been achieved. The book is organized as follows. Chapters one-four tell a coherent story about the achievements of the sector between 2002 and 2008 (1381-87AC), the financial resources used to achieve the results, and the contribution the private sector has made to the achievements. Chapters five-eight) look forward. They identify the challenges the sector is facing in meeting human resource needs, expanding the coverage of the basic package of health services (BPHS), and increasing the institutional capacity of the Ministry of Public Health (MoPH). Chapter eight summarizes the lessons learned and provides options for moving forward.